The Diversity of Monocotyledone Plants in Pu Hoat Nature Reserve, Nghe An Province - Hung, Nguyen Danh; Hoi, Tran Minh; Thuong, Nguyen Thi Hoai; Dai, Do Ngoc (VNU Journal of Science: Natural Sciences and Technology, 2019)
The Monocotyledone in Pu Hoat Nature Reserve (Nghe An province) was surveyed and 432 species of 173 genera and 37 families were identified, adding 260 species, 76 genera and 8 families to the 2013 Pu Hoat plant list. There are 22 Monocotyledone species on Pu Hoat plant list reported threatened and listed in the Red Data Book of Vietnam (2007). The useful plant species of the Pu Hoat Monocotyledone are categorized as follows: 197 species as medicinal plants, 48 species for food and food stuffs, 94 species for ornament, and 38 species for essential oil. The Monocotyledone species in Pu Hoat Nature Reserve are comprised mainly of tropical elements, accounting for 64.36%, of which, the endemic elements with 23.38%; temperate elements, 6.90%; cultivated elements, 3.24%; unknown elements, 1.85%; and global elements, 0.18%. The Spectrum of Biology (SB) of the flora in Pu Hoat Nature Reserve is summarized as follows: SB = 41.90 Ph + 24.77 Ch + 8.33 Hm + 15.28 Cr + 8.56 Th + 1.16 Hy. Keywords Diversity, Monocotyledone, Pu Hoat, Nature, Plants, Nghe An. References [1] Viện Điều tra Quy hoạch Rừng, Điều tra đa dạng sinh học Pù Hoạt làm cơ sở Thành lập Khu Bảo tồn Thiên nhiên, Vinh, 2013. [2] Lê Thị Hương, Đỗ Ngọc Đài, Đa dạng thực vật và bảo tồn ở Khu Bảo tồn Thiên nhiên Pù Hoạt, Nghệ An, Tạp chí Khoa học và Công nghệ, 50 (2012) 1347-1352. [3] Hoàng Danh Trung, Phạm Hồng Ban, Đỗ Ngọc Đài, Đa dạng thực vật bậc cao có mạch ở vùng đệm Khu bảo tồn thiên nhiên Pù Hoạt, Nghệ An, Tạp chí Nông nghiệp và Phát triển Nông thôn, 16 (2010) 90-94. [4] Sở Khoa học và Công nghệ Nghệ An, Nghiên cứu đa dạng sinh học Khu Bảo tồn Thiên nhiên Pù Hoạt, Nghệ An đề xuất biện pháp bảo vệ, Vinh, 2016. [5] Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, NXB Đại học Quốc gia, Hà Nội, 2007. [6] Nguyễn Tiến Bân, Cẩm nang tra cứu và nhận biết các họ thực vật hạt kín ở Việt Nam. NXB Khoa học và kỹ thuật, Hà Nội, 1997. [7] Phạm Hoàng Hộ, Cây cỏ Việt Nam, Quyển III, NXB Trẻ, TP HCM, 2000. [8] P. Wu, P. Raven (Eds.) et al., Flora of China, Beijing & St. Louis. Vol. 1 (2002) 25. [9] R.K. Brummitt, Vascular plant families and genera, Royal Botanic Gardens, Kew, 1992. [10] Nguyễn Tiến Bân (Chủ biên) et al., Danh lục các loài Thực vật Việt Nam, Tập III, NXB Nông nghiệp, Hà Nội, 2005. [11] C. Raunkiaer, Plant life forms, Claredon, Oxford, 1934. [12] Nguyễn Tiến Bân (Chủ biên) et al., Sách Đỏ Việt Nam (Phần II: Thực vật). NXB. Khoa học tự nhiên và Công nghệ, Hà Nội, 2007. [13] Ly Ngoc Sam, Dang Van Son, Do Dang Giap, Truong Ba Vuong, Do Ngoc Dai, Nguyen D. Hung, ¬¬Zingiber nudicarpum D. Fang (Zingiberaceae) a new record for Vietnam, Bioscience Discovery, 8 (2017) 01-05. [14] Nguyễn Thanh Nhàn, Nghiên cứu đa dạng thực vật VQG Pù Mát và đề xuất các giải pháp bảo tồn, Luận án Tiến sĩ Sinh học, Vinh, 2017. [15] Đặng Quốc Vũ, Nghiên cứu tính đa dạng thực vật làm cơ sở cho công tác bảo tồn tại Khu Bảo tồn thiên nhiên Xuân Liên, Thanh Hóa, Luận án Tiến sĩ Sinh học, Hà Nội, 2016. [16] Võ Văn Chi, Từ điển cây thuốc Việt Nam, Tập I-II. NXB Y học, Hà Nội, 2012. [17] Triệu Văn Hùng (chủ biên), Lâm sản ngoài gỗ ở Việt Nam, NXB Bản đồ, Hà Nội, 2007.